2017
DOI: 10.1186/s13568-017-0510-2
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Chlamydia trachomatis and Mycoplasma spp., but not Neisseria gonorrhoeae and Treponema pallidum, in women undergoing an infertility evaluation: high prevalence of tetracycline resistance gene tet(M)

Abstract: Chlamydia trachomatis, Mycoplasma spp., Neisseria gonorrhoeae and Treponema pallidum are sexually transmitted pathogens that threaten reproductive health worldwide. In this study, vaginal swabs obtained from women (n = 133) that attended an infertility clinic in China were tested with qPCRs for C. trachomatis, Mycoplasma spp., N. gonorrhoeae, T. pallidum and tetracycline resistance genes. While none of vaginal swabs were positive for N. gonorrhoeae and T. pallidum, 18.8% (25/133) of the swabs were positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Macrolide drugs such as azithromycin and fluoroquinolones have been confirmed to have antibacterial activity against C. psittaci in vitro, 26,27 In particular, moxifloxacin has strong antibacterial activity against Chlamydia, and there are case reports at home and abroad that the use of fluoroquinolone drugs is effective. [28][29][30][31] Given the lack of experience in the use of tetracyclines in our hospital, Chlamydia trachomatis, which is the same species as C. psittaci in my country, is highly resistant to tetracycline, 32 so the treatment for case 1 patient used moxifloxacin and it was effective. After five patients were treated, four patients were improved and discharged.…”
Section: Discussionmentioning
confidence: 99%
“…Macrolide drugs such as azithromycin and fluoroquinolones have been confirmed to have antibacterial activity against C. psittaci in vitro, 26,27 In particular, moxifloxacin has strong antibacterial activity against Chlamydia, and there are case reports at home and abroad that the use of fluoroquinolone drugs is effective. [28][29][30][31] Given the lack of experience in the use of tetracyclines in our hospital, Chlamydia trachomatis, which is the same species as C. psittaci in my country, is highly resistant to tetracycline, 32 so the treatment for case 1 patient used moxifloxacin and it was effective. After five patients were treated, four patients were improved and discharged.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, vaginal swabs were collected from 134 women attending Subei People’s Hospital of Yangzhou in China for first or second infertility evaluation. Previous study demonstrated that none of vaginal swabs were positive for Neisseria gonorrhoeae and Treponema pallidum , but 18.8% of these swabs were positive for Chlamydia trachomatis and 17.3% of the swabs were positive for Mycoplasma species by PCRs [ 10 ]. All swabs were positive for tetracycline resistance gene tet (M) which is the most effective antibiotic for bacterial sexually transmitted infections [ 10 ].…”
Section: Main Textmentioning
confidence: 99%
“…Collection and DNA extraction of the human vaginal swabs were performed as described before [ 10 ]. Nucleotides of mcr - 1 , mcr - 2 and mcr - 3 genes in the samples were amplified with primers described before [ 11 ].…”
Section: Main Textmentioning
confidence: 99%
“…Macrolide drugs such as azithromycin and uoroquinolones have been con rmed to have antibacterial activity against C. psittaci in vitro [25,26], In particular, moxi oxacin has strong antibacterial activity against Chlamydia, and there are case reports at home and abroad that the use of uoroquinolone drugs is effective [27][28][29][30]. Given of the lack of experience in the use of tetracyclines in our hospital, Chlamydia trachomatis, which is the same species as C. psittaci in my country, is highly resistant to tetracycline [31], so the treatment for case 1 patient used moxi oxacin and it was effective. After ve patients were treated, four patients were improved and discharged.…”
Section: Discussionmentioning
confidence: 99%